2014
DOI: 10.1126/science.1251121
|View full text |Cite
|
Sign up to set email alerts
|

Feedback control of chromosome separation by a midzone Aurora B gradient

Abstract: Accurate chromosome segregation during mitosis requires the physical separation of sister chromatids before nuclear envelope reassembly (NER). However, how these two processes are coordinated remains unknown. Here, we identified a conserved feedback control mechanism that delays chromosome decondensation and NER in response to incomplete chromosome separation during anaphase. A midzone-associated Aurora B gradient was found to monitor chromosome position along the division axis and to prevent premature chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
190
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(215 citation statements)
references
References 29 publications
22
190
2
Order By: Relevance
“…Furthermore, while failure in cytokinesis following depletion of bona-fide regulators such as Pavarotti results in cells with two comparably sized nuclei, Bin2-treated cells rarely exhibit the typical binucleate phenotype, but rather have single large nuclei or large nuclei with numerous smaller nuclei. Similar to prior observations (Afonso et al ., 2014), Bin2 addition in early anaphase led to rapid mitotic exit and the formation of a single large nucleus (Fig 3A, Supplemental Movies 8, 9). The fact that this Bin2-treated anaphase cell did not complete cytokinesis is likely due to the consequences of rapid mitotic exit as well as the positioning of the nucleus in the midzone position.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, while failure in cytokinesis following depletion of bona-fide regulators such as Pavarotti results in cells with two comparably sized nuclei, Bin2-treated cells rarely exhibit the typical binucleate phenotype, but rather have single large nuclei or large nuclei with numerous smaller nuclei. Similar to prior observations (Afonso et al ., 2014), Bin2 addition in early anaphase led to rapid mitotic exit and the formation of a single large nucleus (Fig 3A, Supplemental Movies 8, 9). The fact that this Bin2-treated anaphase cell did not complete cytokinesis is likely due to the consequences of rapid mitotic exit as well as the positioning of the nucleus in the midzone position.…”
Section: Resultssupporting
confidence: 92%
“…ABK activity is essential for proper cytokinesis (Adams et al ., 2001, Echard et al ., 2004, Eggert et al ., 2004, Smurnyy et al ., 2010) and at anaphase onset the CPC complex re-localizes to the spindle midzone (Adams et al ., 2000), an area comprised of stable overlapping MTs. The midzone-associated CPC generates an activity gradient (Fuller et al ., 2008, Tan and Kapoor, 2011) that helps ensure complete sister chromatid separation (Afonso et al ., 2014), and that is proposed to contribute to cleavage furrow positioning (Adams et al ., 2000, Tan and Kapoor, 2011, Terada, 2001). Aurora A kinase is required for centrosome maturation, separation and function (Giet et al ., 2002, Glover et al ., 1995, Hannak et al ., 2001), proper kinetochore-MT attachment (Bakhoum et al ., 2014, Barisic et al ., 2014, Chmatal et al ., 2015, Ye et al ., 2015), chromosome segregation (Hegarat et al ., 2011), MT nucleation (Scrofani et al ., 2015) and robust assembly of midzone MTs (Lioutas and Vernos, 2013, Reboutier et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PP1c docked on MEL-28 at kinetochores in anaphase may also help counter Aurora B kinase localized at the midzone, which is proposed to restrict nuclear envelope reformation (Afonso et al, 2014). More speculatively, outer kinetochore disassembly by MEL-28-PP1c may be important for replication of centromeric chromatin, whose assembly is coupled to M-phase exit in many species (McKinley and Cheeseman, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PP2A in this process is less characterized. Nonetheless, a recent study showed that a midzone-associated Aurora B gradient monitors chromosome position along the division axis and to prevent premature chromosome decondensation by retaining Condensin I until effective separation of sister chromatids is achieved (Afonso et al ., 2014). Both PP1 and PP2A phosphatases counteract this gradient and promoted chromosome decondensation (Afonso et al ., 2014).…”
Section: Mitosis: Pp2a As a Gatekeeper From Mitotic Entry To Mitotic mentioning
confidence: 99%